Out-of-Reference Range Thyroid-Stimulating Hormone Levels in Levothyroxine-Treated Primary Hypothyroid Patients: A Multicenter Observational Study - YAVUZ, DİLEK (FRONTIERS MEDIA SA, 2017)
Objective: Although levothyroxine (LT4) replacement therapy for hypothyroidism has been established as safe, inexpensive and effective, many studies from different countries reported out-of-reference range thyroid-stimulating hormone (TSH) values for the hypothyroid patients under LT4 treatment. The aim of this study was to determine TSH levels of primary hypothyroid patients under LT4 treatment and to assess self-reported compliance with daily LT4 intake in tertiary care centers in Turkey. Design: In this cross-sectional, observational study, adult patients with primary hypothyroidism, receiving LT4 treatment for at least 6 months, were included. The patients were from 12 tertiary care centers in 9 cities of Turkey. TSH and free T4 levels were recorded from patient files and self-reported compliance with daily LT4 intake was assessed by interviewing the subjects at the last visit. Results: A total of 1,755 subjects (46 +/- 13 years; F/M: 89.9/10.1%) with primary hypothyroidism were enrolled. Of the hypothyroid subjects, 44.8% had out-of-reference range serum TSH levels. TSH values were over the reference range (TSH > 4 mIU/L) in 26.2% and were under the reference range (TSH < 0.5 mIU/L) in 18.6% of the patients. Total duration of LT4 treatment was 5.9 +/- 4.7 years and mean dose was 1.2 +/- 0.6 mu g/kg/day. Non-compliant patients (31.1%) had higher TSH levels (6.9 +/- 16 vs 3.8 +/- 0.9 mIU/L, P = 0.01) compared to compliant patients. Conclusion: The results of this study revealed that nearly half of the hypothyroid patients had out-of-reference range serum TSH values, despite under LT4 treatment. Compliance with LT4 treatment seems to be one of the major determinants to reach the target TSH levels in hypothyroid patients.
Keywords: hypothyroidism; levothyroxine; target thyroid-stimulating hormone; thyroid-stimulating hormone; primary hypothyroidism; compliance; L-THYROXINE; PYLORI INFECTION; ABSORPTION; THERAPY; DISEASE; REPLACEMENT; PREVALENCE; COMMUNITY